2016
DOI: 10.1093/database/baw011
|View full text |Cite
|
Sign up to set email alerts
|

HerDing: herb recommendation system to treat diseases using genes and chemicals

Abstract: In recent years, herbs have been researched for new drug candidates because they have a long empirical history of treating diseases and are relatively free from side effects. Studies to scientifically prove the medical efficacy of herbs for target diseases often spend a considerable amount of time and effort in choosing candidate herbs and in performing experiments to measure changes of marker genes when treating herbs. A computational approach to recommend herbs for treating diseases might be helpful to promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…The species sources of the identified NPs were collected from the respective literatures or by using the NP name/structure to search the TCM-ID ( 22 ), TCM@Taiwan ( 23 ), TCMID ( 25 ), TCMSP ( 26 ), TM-MC ( 27 ), StreptomeDB ( 38 ) and HerDing ( 39 ) databases. While available, we also collected the collection location, earliest collection time (format: Year-Month, such as 2015-MAR), and organism part of the species for extracting the NP.…”
Section: Data Collection and Processingmentioning
confidence: 99%
“…The species sources of the identified NPs were collected from the respective literatures or by using the NP name/structure to search the TCM-ID ( 22 ), TCM@Taiwan ( 23 ), TCMID ( 25 ), TCMSP ( 26 ), TM-MC ( 27 ), StreptomeDB ( 38 ) and HerDing ( 39 ) databases. While available, we also collected the collection location, earliest collection time (format: Year-Month, such as 2015-MAR), and organism part of the species for extracting the NP.…”
Section: Data Collection and Processingmentioning
confidence: 99%
“…GHJTY is a complex herbal decoction composed of 18 plants; therefore, we previously used bioinformatics and screening experiments to select the five medicinal herbs present in GHJTY with the greatest potential to improve the efficacy and convenience of pharmaceutically prescribing GHJTY [ 5 ]. These five medicinal herbs include Ostericum koreanum Maximowicz (Osterici Radix; OK), Lonicera japonica Thunberg (Lonicerae Folium; LJ), Clematis mandshurica Ruprecht (Clematis Radix; CM), Angelica gigas Nakai (Angelicae Gigantis Radix; AG), and Phellodendron amurense Ruprecht (Phellodendri Cortex; PA).…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] It is a complex herbal decoction composed of 18 plants. In order to improve the efficacy and convenience of pharmaceutical prescription, a previous bioinformatics study [ 6 ] identified the 5 medicinal herbs with the greatest potential. These were Ostericum koreanum Maximowicz (Osterici Radix, OK), Lonicera japonica Thunberg (Lonicerae Folium, LJ), Clematis mandshurica Ruprecht (Clematis Radix, CM), Angelica gigas Nakai (AngelicaeGigantis Radix, AG), and Phellodendron amurense Ruprecht (Phellodendri Cortex, PA).…”
Section: Introductionmentioning
confidence: 99%